Validity and effectiveness of dhikr breathing relaxation model therapy on insomnia disorders - Purwanto, Setiyo; Rachmah Nur Anganti, Nisa; Amini Yahman, Soleh (Indigenous, 2022)
Abstract. Insomnia is the most common sleep disorder reported by the public, which impacts disrupting activities during the day and worsening body health. Therefore, interventions are needed to improve the quantity and quality of sleep for the body to be healthier. This study aims to analyze the content validity and the effect of applying dhikr breathing relaxation therapy on insomniacs. This research and development involved five experts/psychologists with a minimum education of a master’s in psychology and nine people with insomnia in their productive age domiciled in Surakarta as the research subjects. Insomnia subjects were chosen using the sequential-random sampling method and selected utilizing the Insomnia Severity Index (ISI). The measuring instrument used was a content validity assessment questionnaire assessed by experts (raters). The content validity analysis employed Aiken's V coefficient, and the effect of the therapy application was analyzed descriptively from qualitative data in the form of interviews a week after the therapy application on the subjects with insomnia. The validation test results obtained an average V value of 0.981. The analysis results showed that the effects of applying the therapy model, in general, had a positive influence on improving sleep quality, characterized by ease of entering sleep, reducing the frequency of awakening during sleep, and waking up refreshed. In conclusion, the dhikr breathing relaxation therapy model has a positive effect on improving sleep quality. This study implies that the dhikr breathing relaxation therapy model is appropriate and feasible to use as a therapy to reduce insomnia symptoms. Keywords: dhikr breathing relaxation; effect; insomnia.